Instrumental Testing of RC Frame Structures for Response and Damage Analysis Before and During the Kahramanmaras Earthquakes on 6th February 2023 - Genes, Mehmet Cemal; Tapia-Hernandez, Edgar; Karimi, Mohammad R. B. (Springer International Publishing Ag, 2025)
On February 6, 2023, a sequence of earthquakes strucked the province of Gaziantep, Turkey, affecting eleven provinces in Turkey and some in Syria. The earthquakes caused significant casualties as many buildings either totally or partially collapsed. This paper focuses on the performance of one building before and during the seismic sequence. Forced vibration tests were conducted on one seven-story reinforced concrete (RC) frame building in Antakya in 2007. The dynamic properties were determined from the readings, allowing the calibration of a detailed 3D model in OpenSees. Nonlinear dynamic analyses were conducted using the analytical model under a set of ground motions recorded during the earthquake. The structural and non-structural damage in the analyses was related to the findings in the field inspections.
11th International Conference on Experimental Vibration Analysis for Civil Engineering Structures-EVACES -- JUL 02-04, 2025 -- Porto, PORTUGAL
Keywords: Structural monitoring; damage assessment; 6(th) February 2023 Earthquakes; Non-structural damage; earthquake